Integration of Environmental Education for Sustainable Agriculture: Status in Tertiary Institutions and Guidelines for Institutional Policies and Curriculum Management - De La Cruz, Dina S. (2000)
The study aimed to: 1) ascertain the current status of environmental education (EE) for sustainable agriculture (SA) in 12 selected tertiary institutions in Luzon, Philippines, and 2) develop a set of guidelines for institutional policies and curriculum management for the integration of EE into the curriculum for SA. A questionnaire-guided interview of 27 educational administrators and j'4 curriculum planners from the institutions was conducted for data collection. Data were analyzed by frequency counts, percentages, means and standard deviations. The status of the integration of EE into the curriculum for SA was rated by respondents as "medium" level. Tertiary institutions offered EE and SA as separate courses in their curricula and more EE courses were offered than SA courses. Respondents agreed to support the implementation of a clearly defined policy for the integration of EE into the curriculum for SA. All (12) tertiary institutions have good number of qualified and available teaching staff. Teaching materials were available for appropriate teaching processes, although these must be further improved in terms of quantity and quality.